The impact of self-as-a-model interventions on children's self-regulation of learning and swimming performance - Clark, S. E.; Ste-Marie, D. M. (Journal of Sports Sciences, 2007)
We compared two self-as-a-model interventions: self-modelling (viewing oneself perform an adaptive behaviour) and self-observation (viewing oneself perform at current skill level). Operating within Zimmerman's (1989, 2000) theory of self-regulated learning, we examined the effect of the modelling interventions on three self-regulatory processes (self-efficacy, intrinsic motivation, and self-satisfaction), as well as physical performance. Thirty-three children were randomly assigned to one of three experimental groups. The two self-as-a model groups received the modelling intervention just before physical practice, whereas the control group received physical practice only. Analyses of the retention scores revealed significant differences for all dependent measures. Post hoc testing showed consistently that the self-modelling group performed better than the self-observation and control groups, and that the two latter groups performing similarly. These results provide support for the implementation of self-modelling interventions with children when teaching motor skills.